EU COMMON AGRICULTURAL POLICY AND PRE-ACCESSION ASSISTANCE MEASURES FOR RURAL DEVELOPMENT - Vapa Tankosić, Jelena; Stojsavljević, Miroslav (Economics of Agriculture, 2014)
Common Agricultural Policy is one of the keystones of European Union. This paper explores the functioning and the course of reforms of the Common Agricultural Policy of the European Union, as well as potentials of Instruments for Pre-Accession Assistance, for improving agriculture and ensuring rural development in candidate countries. Successful adoption and implementation of European Unions agricultural standards and values in future member countries largely depends on proper implementation of standards and mechanisms necessary for using pre-accession assistance instruments. In this paper current situation in Republic of Serbia, as candidate country is compared to experiences of the Republic of Croatia from the period before full membership status, and the Republic of Slovenia as a member state. The conclusions of the paper confirm the hypothesis, that the Republic of Serbia must establish network of bodies for using pre-accession assistance instruments, which requires numerous changes in the structure and organization of the agricultural sector.